Implementation of Guidelines on Prevention of Coercion and Violence (PreVCo) in Psychiatry: Study Protocol of a Randomized Controlled Trial (RCT) - Steinert, Tilman; Bechdolf, Andreas; Mahler, Lieselotte; Muche, Rainer; Baumgardt, Johanna; Bühling-Schindowski, Felix; Cole, Celline; Kampmann, Marie; Sauter, Dorothea; Vandamme, Angelika; Weinmann, Stefan; Hirsch, Sophie (Frontiers in Psychiatry, 2020)
Background: Coercive measures are among the most controversial interventions in psychiatry. There is a large discrepancy between the sheer number of high-quality guidelines and the small number of scientifically accompanied initiatives to promote and evaluate their implementation into clinical routine. In Germany, an expert group developed guidelines to provide evidence- and consensus-based recommendations on how to deal with violence and coercion in psychiatry. Methods: The study presented examines whether coercive measures on psychiatric wards can be reduced by means of an operationalized implementation of the guidelines "Prevention of coercion: prevention and therapy of aggressive behavior in adults". Out of a set of 12 interventions offered, wards are free to choose three interventions they want to implement. The primary outcome is the number of coercive measures per bed and month/year. Secondary outcomes are cumulative duration of coercive measures per bed and month/year. The most important control variable is the number of aggressive incidents. We plan to recruit 52 wards in Germany. Wards treating both voluntary and compulsorily admitted patients will be included. A 1:1 stratified randomized controlled trial will be conducted stratified by the amount of coercive measures, aggressive assaults and implemented aspects of the guidelines. In addition to the control group analysis, a waiting list design allows a pre-post analysis for all participating wards of the waiting list group. A parallel qualitative study will examine factors related to successful implementation and to successful reduction of coercion as well as relevant barriers. Discussion: We are planning a nationwide study on the implementation of evidence- and consensus-based guidelines in psychiatric hospitals. This study intends to promote the transfer of expert knowledge as well as results from clinical trials into clinical routine with the potential to change supply structures in mental health sector. Trial registration: “Implementation of the German Clinical Practice Guidelines on Prevention of Coercion and Violence (PreVCo)” was prospectively registered with ISRCTN registry (displayed on the public web site www.isrctn.com, registration number ISRCTN71467851) under the working title “Implementation of clinical practice guidelines on prevention of coercion in adult's psychiatry in Germany [Implementierung der S3 Leitlinie Verhinderung von Zwang (IVZ S3)]”.